2000
DOI: 10.7863/jum.2000.19.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Non-Asian hepatocellular carcinoma: correlation between histologic features and echogenicity.

Abstract: Studies of hepatocellular carcinoma in Asia have revealed a correlation between lesion hyperechogenicity and five histologic features: nonliquefied necrosis, sinusoidal dilatation, hemorrhage, fatty metamorphosis, and fibrosis. However, this correlation has not been investigated for non-Asian hepatocellular carcinoma, despite substantial differences between the Asian and non-Asian forms of this carcinoma. We retrospectively reviewed records of 29 patients seen at one United States institution who had hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Correlating the ultrasound findings with the histologic observations, they observed that hypo-echoic lesion corresponded to solid tumor without necrosis, complex lesion corresponded to tumor with partial necrosis and hyperechoic lesion corresponded to fatty metamorphosis or sinusoidal dilatation. Working also on hepatocellular carcinoma, developed this time on non-Asian patients, Wachsberg et al 16 have correlated the apparent echogenic character (hyper-or hypo-echoic) of the lesion with the number of different histologic features detected (nonliquefied necrosis, sinusoidal dilatation, fatty metamorphosis, hemorrhage and fibrosis). Contrary to the results of Tanaka et al, 15 they did not find any significant correlation between these 2 kinds of parameters in the 29 lesions studied.…”
Section: Discussion/conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…Correlating the ultrasound findings with the histologic observations, they observed that hypo-echoic lesion corresponded to solid tumor without necrosis, complex lesion corresponded to tumor with partial necrosis and hyperechoic lesion corresponded to fatty metamorphosis or sinusoidal dilatation. Working also on hepatocellular carcinoma, developed this time on non-Asian patients, Wachsberg et al 16 have correlated the apparent echogenic character (hyper-or hypo-echoic) of the lesion with the number of different histologic features detected (nonliquefied necrosis, sinusoidal dilatation, fatty metamorphosis, hemorrhage and fibrosis). Contrary to the results of Tanaka et al, 15 they did not find any significant correlation between these 2 kinds of parameters in the 29 lesions studied.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Forty-two tumors were generated by subcutaneous injection of 2 ϫ 10 6 cells into dorsa of 6-to 8-week-old C57BL/6 mice. Ultrasound examinations were performed on all tumors on days 7,9,11,14,16,18, and, 21 after transplantation. On the day of the examination, 6 mice were randomly killed, and the tumor was taken for histologic analysis.…”
Section: Protocol 3: Sonographic Quantification Of Necrosis and Compamentioning
confidence: 99%
“…On imaging, non-Asian HCC seems to be much less steatotic than Asian HCC. 65 Although the discrepancy in the prevalence of fatty change between Asia and the West may suggest the presence of unknown environmental factors in hepatocarcinogenesis, a comparative study of fatty change in small HCCs and DNs is necessary to confirm the presence of such a discrepancy. The developmental mechanism of fatty change in early-stage HCC is still controversial.…”
Section: Early Hepatocellular Carcinomamentioning
confidence: 99%
“…Although Rouffiac et al 33 have quantified the correlation between echogenicity and the degree of melanoma necrosis, the parametric intratumoral pattern necessary to visually differentiate necrotic from viable tissues has not been reported. Two HCC sonography studies 34,35 have been performed in an effort to correlate the echogenic characteristics of focal liver lesions with different histologic features. However, discrepant results were reported when attempting to correlate echogenic features with tumor histology.…”
Section: Deng Et Almentioning
confidence: 99%